Interplanetary magnetic Taylor microscale and implications for plasma dissipation - Matthaeus, W.H. (2008)
The Taylor microscale, a measure of mean square spatial derivatives, is evaluated for interplanetary magnetic field fluctuations from single- and multiple-point data using Cluster and ACE spacecraft data. The Taylor scale is compared to the measured inner scale, which for hydrodynamics would correspond to the Kolmogorov scale. The results are not consistent with dissipation of the hydrodynamic type, and indicate that solar wind dissipation involves kinetic plasma physics at both proton and electron scales. © 2008. The American Astronomical Society. All rights reserved.